Analytical model for helical particle array assessment for EMI shielding applications - Ayoub Hamidi; Ahmad Cheldavi; Asghar Habibnejad Korayem; Mohammad Baharian (Scientific Reports)
Abstract This paper introduces an analytical method for studying power transmission through an infinite array of helical-shaped metal particles in a lossy dielectric medium. While the assessment of composite slabs’ transmitted power has been extensively researched in the electromagnetic interference (EMI) shielding field, many studies lack an adequate problem description. The primary inadequacy of these studies is the need for an analytical framework. This study, besides presenting a new approach to designing a concrete composite that leverages the magnetoelectric properties of the particles, making it suitable for EMI shielding, also employs a theoretical method to analyze the composite. A circuit model of the array is introduced using a modal field decomposition, which justifies the impact of helix transmission modes and the transverse magnetic field component on the shielding properties of the array. It is also shown that the resonances of the array can be tuned by engineering the helix properties. Furthermore, to broaden the applicable bandwidth of the composite, a multi-layer structure is proposed. The computational load of the proposed method demonstrates exceptional speed due to its circuit model foundation. The model yields valuable results compared to experimental measurement, making it ideal for optimizing various shielding composite structures for EMI shielding applications.